2022
DOI: 10.12997/jla.2022.11.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Treatment for Patients With Familial Hypercholesterolemia

Abstract: Familial hypercholesterolemia (FH) is one of the most common and, therefore, important inherited disorders in preventive cardiology. This disease is mainly caused by a single pathogenic mutation in the low-density lipoprotein receptor or its associated genes. Moreover, it is correlated with a high risk of cardiovascular disease. However, the phenotype severity even in this monogenic disease significantly varies. Thus, the current study aimed to describe FH and its importance and the factors (inherited and acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 91 publications
(100 reference statements)
0
2
0
Order By: Relevance
“… 1–3 Although their risk of ASCVDs is extremely high, studies have shown that the individual risk is heterogeneous. 4 We and others have shown that many factors affect the actual individual risk of ASCVDs in patients with FH, such as age, sex, diabetes, hypertension, smoking, the presence of pathogenic variants, high-density lipoprotein (HDL) cholesterol, LDL cholesterol, and plaque load in the coronary arteries as measured by coronary computed tomography (CT). 5–9 These factors, except for the presence of pathogenic variants of FH, are also associated with ASCVDs in individuals without FH.…”
Section: Introductionmentioning
confidence: 99%
“… 1–3 Although their risk of ASCVDs is extremely high, studies have shown that the individual risk is heterogeneous. 4 We and others have shown that many factors affect the actual individual risk of ASCVDs in patients with FH, such as age, sex, diabetes, hypertension, smoking, the presence of pathogenic variants, high-density lipoprotein (HDL) cholesterol, LDL cholesterol, and plaque load in the coronary arteries as measured by coronary computed tomography (CT). 5–9 These factors, except for the presence of pathogenic variants of FH, are also associated with ASCVDs in individuals without FH.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, genotype-guided oral P2Y12 inhibitor use showed no statistically significant benefit to ischemic outcomes [13]. Although there is a growing demand for genotype-guided and personalized pharmacotherapy [14], development has been limited for several reasons, including insufficient evidence of genetic association, replication, and difficulties in conducting clinical trials themselves.…”
mentioning
confidence: 99%